INTEGRATING ARTIFICIAL INTELLIGENCE IN SCALABLE PLATFORM DEVELOPMENT: STRATEGIC LEADERSHIP FOR FUTURE-READY SYSTEMS - Shishir Biyyala (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This comprehensive article explores the strategic integration of Artificial Intelligence (AI) in scalable platform development, focusing on the critical role of engineering leadership in navigating this complex technological landscape. The article examines the current state of AI technologies relevant to platform development, discusses advanced system integration techniques, and addresses the challenges of incorporating AI into existing infrastructures. It emphasizes the importance of fostering collaboration between AI specialists and system architects, proposing strategies for building cross-functional teams and facilitating business alignment. The article delves into AI-driven approaches for enhancing platform scalability, reliability, and performance, including optimization techniques, predictive maintenance, and adaptive resource allocation. Furthermore, it outlines best practices for engineering leaders in developing AI integration roadmaps, managing risks and ethical considerations, and implementing continuous learning strategies. The article concludes by exploring future trends and opportunities in AI, providing insights into emerging technologies and long-term strategies for maintaining competitive advantage. Through a synthesis of theoretical frameworks, case studies, and industry best practices, this article offers actionable guidance for engineering leaders tasked with steering their organizations through the AI-driven transformation of scalable platforms, ultimately contributing to the development of future-ready systems capable of adapting to the ever-evolving technological landscape.